KONTROL DIRI PADA REMAJA PENGHAFAL AL-QUR’AN DI PONDOK PESANTREN MODERN MUHAMMADIYAH BOARDING SCHOOL (MBS) 2 YOGYAKARTA - Nining Mirsanti (UIN Sunan Kalijaga Yogyakarta, 2020)
This article discusses the self-control of adolescents who memorize the Koran at the Muhammadiyah Boarding School (MBS) Modern Islamic Boarding School 2 Yogyakarta. The research method used is a qualitative method of phenomenological approach through interviews with two subjects. The results of the study indicate that good self-control is very necessary for Al-Quran memorizing santri especially for teenagers who have many challenges. Challenges faced by the santri at the Muhammadiyah Boarding School (MBS) 2 Yogyakarta Modern Islamic Boarding School, such as the influence of immorality and listening to music that is not Islamic in nature, can be overcome by cultivating self-motivation about the benefits of memorizing the Koran, repeating memorization, routinely listen to and read the Koran.Keywords: Self Control, Youth, Al-Quran